Estimation of an econometric model that relates the crime of contraband with the devaluation of the Colombian peso and Peruvian sol - Abril-Donoso, Mauricio (2019)
The objective of the study is to explain the behavior of the crime of contraband, based on the devaluations of the Colombian and Peruvian currencies. The information was collected from the allegations of contraband of the base of crimes of the Fiscalía General de Estado de Ecuador (FGE), the monthly quotes were also collected on average reached by the Colombian Peso of the Financial Superintendence of Colombia (www.superfinanciera.gov.co) and the Peruvian sol of the website investing.com (https://es.investing.com/currencies/usd-pen-historical-data). The results show the correct estimation of the econometric model for the contraband, in addition to how the explanatory variables generate the commission of the crime of contraband, this will allow the governmental authorities to take economic measures to protect the internal and external market of the Country.